Humanitarian supply chain management: a systematic review and bibliometric analysis. (14th January 2021) - Dhamija, Pavitra; Gupta, Shivam; Bag, Surajit; Gupta, M.L.
The concept of humanitarian operations sustains on the belief that people who are affected by disasters or any other type natural calamity or conflicts possess every right to be assisted and live a dignified life at par with the people leading a normal life. The numbers of disasters are increasing at large. This allows humanitarian supply chain management as one of the upcoming areas for research. This study has considered 241 published papers chosen from the last ten years covering topics of humanitarian logistics, disaster management, humanitarian relief operations etc. The inferences have been drawn out by using bibliometric and network analysis to recognise top contributing authors, keyword search, and countries. The application of citation analysis through PageRank could deliver the most acceptable work in this area. Further, six clusters have been identified that shares current and future scope of humanitarian research in context of supply chain management.